1983
DOI: 10.1128/aac.23.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylprednisolone on entry of ampicillin and gentamicin into cerebrospinal fluid in experimental pneumococcal and Escherichia coli meningitis

Abstract: The influence of methylprednisolone on the passage of ampicillin and gentamicin into and activity within cerebrospinal fluid was examined in two models of experimental meningitis. Steroid pretreatment reduced the concentrations of these drugs in purulent cerebrospinal fluid of rabbits with experimental pneumococcal and Escherichia coli meningitis (P < 0.05). However, the resultant mean concentrations of these antibiotics in cerebrospinal fluid still exceeded the minimal bactericidal concentrations of the infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The present study demonstrates that the penetration of amikacin into the CSF is highly dependent on the degree of meningeal inflammation, as assessed by the degree of hypoglycorrhachia. This is consistent with findings for amikacin and other aminoglycosides in animal models of meningitis (18,19). Previous clinical studies found that aminoglycoside penetration of the blood-brain barrier was poor.…”
supporting
confidence: 81%
“…The present study demonstrates that the penetration of amikacin into the CSF is highly dependent on the degree of meningeal inflammation, as assessed by the degree of hypoglycorrhachia. This is consistent with findings for amikacin and other aminoglycosides in animal models of meningitis (18,19). Previous clinical studies found that aminoglycoside penetration of the blood-brain barrier was poor.…”
supporting
confidence: 81%
“…Although dexamethasone was administered to all patients and CSF vancomycin levels varied widely, we can not exclude the possibility that it had some importance in our vancomycin therapy failures by impairing BBB vancomycin penetration. In experimental models of meningitis, corticosteroids have been shown to reduce meningeal inflammation (22), permeability of the BBB (16), and peak CSF concentrations of multiple antimicrobial agents (25); dexamethasone has rarely been associated with human therapeutic failures (2). However, its recent usage as an early therapeutic adjunctive to cefuroxime or ceftriaxone in a high number of cases of bacterial meningitis in infants and children has not been associated with delayed sterilization of CSF or a significant rate of relapses (21).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of methylprednisolone or dexamethasone on water content of the brain, CSF pressure, and lactate con- (132).…”
Section: Adjunctive Therapeutic Strategiesmentioning
confidence: 99%